Design and Evaluation of Lovastatin Solid Dispersions Incorporated Trilayer Matrix Tablets (International Journal of Pharmaceutical Sciences and Drug Research, 2020)
The current work is aimed to design, prepare and evaluate the trilayer matrix tablets incorporated with lovastatin solid dispersion (SD) for extend drug release. The lovastatin SD prepared by using solvent evaporation technique with varying amounts of polymers (GMS II, Soluplus, Kolliphor ELP, PEG 2000 and Urea) for enhancing the drug solubility. All the formulations examined for physicochemical parameters are within the permissible limits. The optimized SD formulation was incorporated into trilayer matrix tablets which were prepared using different polymers (HPMC 15M & K100M, Chitosan, xanthan gum) by direct compression method for sustaining the drug release. The drug dissolution of optimized lovastatin SD formulation SD15 (drug, soluplus and SLN) was 99.88±5.32% within 60 min which is higher than pure drug 47.33±2.25% and other formulations. The FT-IR, XRD and SEM data assure the compatibility of drug and excipients and amorphous nature of lovastatin. The solid dispersions were further incorporated in to trilayer matrix tablets with active layer and barrier layers. Eight formulations of lovastatin trilayer matrix tablets (AF9-HF9) designed and checked for pre compression parameters. Formulation GF9 demonstrated highest drug release of 99.41±5.28% for 24 hours sustainably over an extended period of time and excellent flow properties. The release order kinetics data indicate the zero order release with highest R2 of 0.9957 for GF9, superior than market extended release formulation (R2=0.9934). All the formulations showed best fit to Higuchi model and Korsmeyer-Peppa’s model indicating diffusion and non-Fickian diffusion process of drug release. GF90 was found to be stable for 180 days at accelerated conditions. Hence the solubility, dissolution rate of lovastatin was enhanced by SD technique further incorporated in to trilayer matrix tablets for sustainable extended drug release upto 24 h.